Design and Manufactering of an X-Band Horn Antenna using 3-D Printing Technology - Toy, Yunus Can; Mahouti, Peyman; Gunes, Filiz; Belen, Mehmet A. (IEEE, 2017)
Herein, design and manufacturing of an X-band pyramid horn antenna using 3-D printer is studied with its experimental results. X-band is used for the military purposes with the marine and satellite technology based on the geographic discovery. Horn antennas are especially very preferable in these applications since they can be built easily at the different types depending on their utilizations and provide low voltage standing wave ratios. This work is focused on a pyramid horn antenna design and its manufacturing method with 3-D printer technology. The measurement results of the 3-D printed antenna are also compared with the simulation results.
Keywords: 3D Printing; Horn Antenna; X band; Engineering; Remote Sensing